From a Smart House to a Connected City: Connecting Devices Services Everywhere - de Lima, João Paulo Cardoso; Becker, Leandro Buss; Siqueira, Frank; Morales, Analucia Schaffino; de Araújo, Gustavo Medeiros (Anais do Simpósio Brasileiro de Computação Ubíqua e Pervasiva (SBCUP); 2016: Anais do VIII Simpósio Brasileiro de Computação Ubíqua e PervasivaDO - 10.5753/sbcup.2016.9451, 2016)
The growing development of smart devices makes it possible to create new distributed applications targeted for smart spaces. The design of intelligent spaces assumes that there is an infrastructure to support the applications requirements. Many academic works have proposed middlewares that provide an abstraction for the use of network services. The network services of an smart space, such as an automated home, can have different communications interfaces. Accordingly, we developed a middleware called UDP4US (Universal Device Pipe for Ubiquitous Services) which was designed to abstract different patterns of communication, keeping the discovery of devices on a local network services. In this paper, we present a new UDP4US architecture component that aims to expose the local network devices services to the Internet. The new component was developed with the REST technology, thus the devices services can be discovered and accessed over the Internet. The new component was exhaustively tested in order to find the liits of its effectiveness. The evaluation of the new component was performed by measuring its discovery and execution times plus the success rate of the services execution exposed over the Internet. The results from the present work are important to guide a better design of distributed applications for smart places.